2019
DOI: 10.1111/gtc.12711
|View full text |Cite
|
Sign up to set email alerts
|

Loss of C/EBPδ enhances apoptosis of intestinal epithelial cells and exacerbates experimental colitis in mice

Abstract: Inflammatory bowel diseases (IBDs) are characterized by chronic inflammation involving intestinal tissue damage, which include ulcerative colitis and Crohn's disease as major entities. Accumulating evidence suggests that excessive apoptosis of intestinal epithelial cells (IECs) contributes to the development of IBD. It was recently reported that the transcription factor CCAAT/enhancer-binding protein delta (C/EBPδ) is involved in inflammation; however, its role in colitis remains unclear. Here, we found that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…It was reported that excessive intestinal epithelial cell apoptosis disrupted intestinal integrity and permitted the invasion of luminal antigens into the lamina propria, thereby leading to the in ammatory response and release of pro-in ammatory cytokines [34]. The present study showed that IUGR increased the concentrations of pro-in ammation cytokines IL-1β, IL-6, TNF-α in the jejunum and IL-1β, IL-6 in the ileum of IUGR piglets.…”
Section: Discussionsupporting
confidence: 57%
“…It was reported that excessive intestinal epithelial cell apoptosis disrupted intestinal integrity and permitted the invasion of luminal antigens into the lamina propria, thereby leading to the in ammatory response and release of pro-in ammatory cytokines [34]. The present study showed that IUGR increased the concentrations of pro-in ammation cytokines IL-1β, IL-6, TNF-α in the jejunum and IL-1β, IL-6 in the ileum of IUGR piglets.…”
Section: Discussionsupporting
confidence: 57%
“…Our results from the present study showed that the sIgA content in jejunum mucosa significantly decreased when piglets suffered from IUGR, which indicated that IUGR damages the intestinal immune function. It was reported that excessive intestinal epithelial cell apoptosis and uncontrolled oxidative stress in the intestine could result in intestinal dysfunction, thereby leading to the inflammatory response and release of proinflammatory cytokines, such as IL-1 β , IL-6, and TNF- α [ 26 , 27 , 55 ]. The results of the present study suggested that IUGR enhanced the concentrations of proinflammatory cytokines (IL-1 β and TNF- α ) in the jejunum.…”
Section: Discussionmentioning
confidence: 99%
“…IgA can turn to sIgA in cell gaps and then bind to the corresponding antigen to relieve the oxidative damage in the small intestine ( Brandtzaeg, 2002 ). It has been found that excessive intestinal epithelial cell apoptosis damage intestinal integrity resulting in the release of inflammatory cytokines ( Jozawa et al., 2019 ). Based on the current results, IUGR weaned piglets showed increased concentrations of jejunum IL-1β, IL-6, and TNF-α and decreased concentration of jejunum IL-8.…”
Section: Discussionmentioning
confidence: 99%